Hypertensive Response to Exercise as an Early Marker of Disease Development - Wojciech Kosowski; Krzysztof Aleksandrowicz (Biomedicines)
Arterial hypertension is one of the world’s leading risk factors for death and disability. With the number of people living with this disease doubling between 1990 and 2019 from 650 million to 1.3 billion, it is a global burden that increases mortality from cardiovascular and kidney diseases. It is extremely important to use all possible diagnostic methods, indicating the possibility of early detection that subsequently leads to effective prevention of disease development. The phenomenon called hypertensive response to exercise (HRE) is one such method. The HRE is defined as a pathological, excessive increase in blood pressure as a result of exposure to the stressor, which is physical exercise. There is no consensus about precise cutoffs in the definition of this condition, which is most commonly diagnosed based on systolic blood pressure (SBP) ≥ 210 mm Hg in men and ≥190 mm Hg in women at peak exercise intensity. The fact that exercise hypotension is a pathologic sign is universally accepted. Accumulating data deliver the information that HRE is also connected to higher overall cardiovascular risk. It was demonstrated that HRE is associated with functional and structural impairment of the left ventricle and the future development of hypertension. HRE should act as a warning signal of increased cardiovascular risk, leading to the need for profound clinical care.